Multisystemic neurodegeneration caused by biallelic pentanucleotide expansions in RFC1. (February 2022) - Herrmann, Laura; Gelderblom, Mathias; Bester, Maxim; Deininger, Natalie; Schütze, Thorsten; Hidding, Ute; Gross, Caspar; Buena-Atienza, Elena; Dufke, Claudia; Gerloff, Christian; Haack, Tobias B.; Zittel, Simone
Highlights: Biallelic RFC1 repeat expansions are a frequent cause of late-onset ataxia. Three out of four patients with RFC1 repeat expansion presented cognitive impairment. Spinal cord atrophy was noticed in all four CANVAS patients. The central motor conduction time was prolonged in one CANVAS patient. Pyramidal tract degeneration may be an additional feature of CANVAS.